Scoping cost and abatement metrics for biomass with carbon capture and storage — the example of bioCCS in cement. (May 2023) - Tanzer, Samantha Eleanor; Blok, Kornelis; Ramírez, Andrea Ramírez
HIGHLIGHTS: System boundary choices vary widely in literature on bioenergy with CCS. System boundary choice can be a major determiner of estimated CO2 avoidance cost Costs and lifecycle greenhouse gas estimated for bioenergy with CCS at cement plant System boundary choice varied net CO2 estimates from -660 to 16 kg CO2 (eq)/t cement Aligned boundaries shrinks avoidance cost range from 48-321€ to 157-193€/t CO2 (eq) Abstract: Negative emission technologies such as biomass with carbon capture and storage (bioCCS) may become an important instrument to limit global warming. Currently, estimates of CO2 avoidance cost for bioCCS vary widely. Using a case study of a cement plant, this paper illustrates how this variance is partially attributable to the system boundary choices made by modellers. The estimated avoidance cost for the bioCCS-in-cement plant ranged from 48-321€2017 /t CO2 (eq) and the net CO2 (eq) from -660 to 16 kg CO2 (eq)/t cement, without any change in the technological model, equipment and input costs, or lifecycle emissions, but by changing the system boundaries used for cost and emission accounting, reflecting the different boundaries seen in bioCCS literature. To allow for more comparable bioCCS cost estimates, studies should always account for costs and emissions of both biomass production and the full chain of carbon capture, transport, and permanent storage, as both are fundamental to the role of bioCCS as a potential "negative emission technology". We also advocate for clear decomposition of metrics, separation of "avoided emissions" from physical flows of greenhouse gases; and explicit consideration of the temporality of the bioCCS system. With these guidelines, the range of avoidance cost of the bioCCS-in-cement plant shrinks to 157-193€2017 /t CO2 (eq) for near-term estimates and to 89-107€2017 /t CO2 (eq) for longer-term estimates. Graphical Abstract: Image, graphical abstract